Electromechanical components for electronic equipment. Basic testing procedures and measuring methods. Mechanical tests on contacts and terminations. Test 16t. Mechanical strength (wired termination of solderless connections) Part 16-20, (15th April 1997) - British Standards Institution,
No abstract available